Mechanisms linking obesity to hypertension - Dorresteijn, J. A. N; Visseren, F. L. J; Spiering, W (Obesity reviews, 2012)
Obesity‐related hypertension is increasingly recognized as a distinct hypertensive phenotype requiring a modified approach to diagnosis and management. In this review rapidly evolving insights into the complex and interdependent mechanisms linking obesity to hypertension are discussed. Overweight and obesity are associated with adipose tissue dysfunction, characterized by enlarged hypertrophied adipocytes, increased infiltration by macrophages and marked changes in secretion of adipokines and free fatty acids. This results in chronic vascular inflammation, oxidative stress, activation of the renin‐angiotensin‐aldosterone system and sympathetic overdrive, eventually leading to hypertension. These mechanisms may provide novel targets for anti‐hypertensive drug treatment. Recognition of obesity‐related hypertension as a distinct diagnosis enables tailored therapy in clinical practice. This includes lifestyle modification and accommodated choice of blood pressure‐lowering drugs.